Liberals and conservatives respond divergently to stereotype portrayals of race and gender - Elizabeth Q. Jiang; Margaret J. Shih (Communications Psychology)
Abstract Representation in the media has become a polarizing issue dividing conservatives and liberals in the U.S. In four experiments (N = 5125), we find that stereotype portrayal elicits divergent attitudinal, economic, and behavioral reactions from liberals and conservatives. Notably, these reactions differ when portrayals feature racial minority (Study 1, n = 958 & Study 2, n = 900) versus white models (Study 3, n = 783 & Study 4, n = 2484). Our findings demonstrate consistent divergence in responses to stereotype congruent versus incongruent portrayals between liberals and conservatives, although the direction and magnitude of differences vary. Liberals and conservatives display both variability and consistency in their divergent evaluations: liberals endorse portrayals of minority races and of incongruency but withhold this endorsement for solely white models, whereas conservatives typically prefer congruent portrayals, but show an openness towards incongruency when white models are featured. Understanding these dynamics is crucial for navigating the current sociopolitical landscape, especially in contexts where representations of race and gender identities are contentious.